2010
DOI: 10.3354/meps08524
|View full text |Cite
|
Sign up to set email alerts
|

Diel vertical migration patterns in juvenile cod from the Skagerrak coast

Abstract: We demonstrated a clear year-round diel vertical migration pattern (DVM) of small (26 to 45 cm) Skagerrak coastal cod Gadus morhua on a small geographic scale. Generalized additive models (GAMs) were used to make inferences about depth movements from a large data set of repeated depth measurements of cod fitted with acoustical tags. The general pattern in vertical behaviour was closely linked to sunrise and sunset, and the timing varied with the length of the day. The absolute magnitude of vertical movement wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…data). Similar seasonal movements to deep water have been observed in Atlantic cod (Hanson 1996, Comeau et al 2002, Cote et al 2004, Espeland et al 2010. Importantly, however, plasma antifreeze levels in juvenile cod are significantly higher than in adults during winter conditions (Kao & Fletcher 1988, Goddard et al 1992.…”
Section: Discussionsupporting
confidence: 52%
“…data). Similar seasonal movements to deep water have been observed in Atlantic cod (Hanson 1996, Comeau et al 2002, Cote et al 2004, Espeland et al 2010. Importantly, however, plasma antifreeze levels in juvenile cod are significantly higher than in adults during winter conditions (Kao & Fletcher 1988, Goddard et al 1992.…”
Section: Discussionsupporting
confidence: 52%
“…The upper 5–7 m are composed of rocky bottoms covered by macroalgae or sandy bottoms with eelgrass (Espeland et al. ). The deepest areas (5–40 m) consist mainly of mud flats with sparse vegetation (Espeland et al.…”
Section: Methodsmentioning
confidence: 99%
“…The deepest areas (5–40 m) consist mainly of mud flats with sparse vegetation (Espeland et al. ). Three channels allow fish to move to and from the bay.…”
Section: Methodsmentioning
confidence: 99%
“…This gear is designed to be set in shallow (about 1 to 5 m) depth, and so bottom depth should be comparable among the samples. In any case, recent telemetry data have shown that cod in the Skagerrak region display a marked diurnal vertical migration pattern, visiting the most shallow (< 5 m) near-shore habitats during nighttime and retreating to deeper habitats during the day (Espeland et al 2010). This pattern is visible for both juvenile cod and larger mature cod.…”
Section: Discussionmentioning
confidence: 98%